Vinhos varietais syrah e tempranillo do vale submédio do São Francisco: ênfase no perfil fenólico e composição de minerais e potenciais marcadores de tipicidade - Dantas, Dayene Louyse Lírio (2023)
The São Francisco Valley (SFV) sub medium region, located between the Brazilian states of Bahia and Pernambuco, stands out from other wine-growing regions in Brazil because it presents a differentiated viticulture as a semi-arid tropical climate, high insolation index, low rainfall index and water available for irrigation that allow up to two harvests per year. The wines made from the Vitis vinifera Syrah and Vitis vinifera Tempranillo cultivars occupy first and second place, respectively, in the production of red grapes in the SFV. In this sense, this study aimed to quantify the phenolic profile, sugars, organic acids and antioxidant capacity of commercial Syrah and Tempranillo wines made in the SFV and to compare them with commercial wines of the same cultivars from wineries of South Africa, Spain, Chile, and Australia. Then, the minerals Potassium, Magnesium, Manganese, Copper, and Zinc were quantified by Atomic Absorption Spectrometry from Syrah and Tempranillo wines made from four different wineries in the SFV and 2014, 2016, 2017, 2018, 2019, and 2021 vintages. In addition, compounds were identified by means of Nuclear Magnetic Resonance (1H NMR) to obtain a fingerprint of tropical wines. In total, 25 phenolic compounds were quantified and classified into chemical groups in all wines (phenolic acids, flavanones, flavan-3-ols, flavonols, anthocyanins, and stilbenes). Among these, catechin, procyanidins B1 and B2, lactic acid, and antioxidant capacity were highlights for tropical SFV wines when compared to wines from temperate regions, according to Principal Component Analysis (PCA). The minerals quantified in the wines were in concentrations within acceptable limits, and the elements order of abundance was the same for all samples: K > Mg > Mn > Cu > Zn. By 1H NMR, the main constituents of the SFV wine samples identified were glycerol, lactic and succinic acids. The alcohol 2,3-butanediol, important for the aromatic properties of wines, was identified in all Tempranillo samples and only in the 2014 vintage of Syrah. In this context, the data reported here contribute to the knowledge of the quality of red wines produced in tropical climate regions of Brazil, such as the SFV, with phenolic compounds, antioxidant capacity and some metabolites being possible markers of typicity, which can be useful for the international recognition of wines from the IP-São Francisco Valley sub medium region.